Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1137/100785429
|View full text |Cite
|
Sign up to set email alerts
|

Testing Fourier Dimensionality and Sparsity

Abstract: Abstract. We present a range of new results for testing properties of Boolean functions that are defined in terms of the Fourier spectrum. Broadly speaking, our results show that the property of a Boolean function having a concise Fourier representation is locally testable. We first give an efficient algorithm for testing whether the Fourier spectrum of a Boolean function is supported in a low-dimensional subspace of F n 2 (equivalently, for testing whether f is a junta over a small number of parities). We nex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
44
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 21 publications
(16 reference statements)
2
44
0
2
Order By: Relevance
“…It is shown that r-sparsity and k-dimensionality are constantquery testable in [13]. As a corollary of Theorem 4, these properties are tolerantly constant-query testable.…”
Section: Introductionmentioning
confidence: 84%
See 4 more Smart Citations
“…It is shown that r-sparsity and k-dimensionality are constantquery testable in [13]. As a corollary of Theorem 4, these properties are tolerantly constant-query testable.…”
Section: Introductionmentioning
confidence: 84%
“…Proof sketch of Theorem 1.1 We prove our main theorem in a similar manner to the implicit learning method used in [14] and [13]. Similarly to [13], our algorithm finds all the large Fourier coefficients of the unknown function f using an implicit version of the Goldreich-Levin algorithm [15]; we call our algorithm Implicit Sieve.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations